Preparation method of colloidal silicon dioxide
By using an organic base to hydrolyze alkoxysilane in ultrapure water and adding a stabilizer, high-purity colloidal silica nanoparticles are prepared, which solves the problem of contamination by metal impurities and anionic impurities in the existing technology and achieves high Preparation of colloidal silica with good purity and alkali resistance, suitable for industrial scale production.
Patent Information
- Application Number
- CN202411609355.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-21
AI Technical Summary
In the existing colloidal silica preparation methods, it is difficult to completely remove metal impurities and anionic impurities, resulting in a decrease in yield after polishing of semiconductor chips, and the process is complex and costly, making it not suitable for industrial scale production.
The organic base solution is used in ultra -pure water hydrolytoxyxilane, adds a stabilizer to form a hydrolysis solution, and prepares high -purity colloidal silicon nanoparticles through the steps of warming and dripping hydrolyzed solution to avoid using inorganic acid to avoid using inorganic acid Or the problem of impurities pollution and hydrolyzed solution caused by organic acids.
The preparation of high -purity colloidal silica is achieved. The total metal impurities content is less than 0.4ppm, and the alkali resistance is good. It is suitable for the polishing process of semiconductor chip, which simplifies the process steps, reduces costs, and is suitable for large -scale industrialized production.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nano materials, and in particular relates to a method for preparing colloidal silicon dioxide suitable for being used as a semiconductor abrasive. Background Art
[0002] Colloidal silica is a dispersion of silica nanoparticles in water. In addition to being used as an additive in papermaking, catalysts, coatings, casting, fiber and other fields, it is now widely used as a very important semiconductor grinding material (abrasive) in the chemical mechanical polishing (CMP) process of chips and is an essential key material for chip processing. When used as an abrasive in semiconductor CMP polishing liquid, silica particles are required to have higher purity and dense structure.
[0003] Among the methods for preparing colloidal silica, the ion exchange method, the elemental silicon hydrolysis method and the Stober method are the mainstream.
[0004] The ion exchange method uses water glass (sodium silicate) as raw material. Sodium silicate is exchanged to obtain silicic acid. The silicic acid undergoes a dehydration condensation reaction under a certain temperature and alkali catalysis to obtain colloidal silica. The ion exchange method can obtain relatively dense nanoparticles and can obtain excellent properties as abrasive particles. However, it cannot completely remove metal impurities such as Al, Fe, Na, and Ca. It is very difficult to reduce the total impurity content to below 10ppm. It can only be used in the first or second step of rough polishing of semiconductor materials that do not require high impurity content. The final step of fine polishing generally requires higher purity colloidal silica, and the total metal content of this silica is generally required to be less than 1ppm or even lower.
[0005] The elemental silicon hydrolysis method uses elemental silicon as the silicon source, and undergoes hydrolysis and condensation reaction under the catalysis of water and alkali to obtain colloidal silicon dioxide. Since the silicon powder will not participate in the reaction completely and it is difficult to remove the incompletely reacted silicon powder, this method will have the problem of silicon powder residue, which limits its application in semiconductor chip polishing.
[0006] The Stober method is to hydrolyze and condense alkoxysilane (methyl orthosilicate, ethyl orthosilicate, etc.) in a mixed solution of water and alcohol under the catalysis of ammonia and other bases to obtain colloidal silica nanoparticles. This method uses organic silicon as a silicon source, with high purity, less metal impurities such as Al, Fe, Na, and Ca, and can obtain ultra-high purity with a total metal content of less than 1ppm, but this method cannot obtain nanoparticles with a dense structure, and the particles have poor alkali resistance. At the same time, the reaction system needs to use a large amount of alcohol organic solvents, which is costly and has poor safety and environmental protection. Some technologies have been improved on this. Patent CN101012060A discloses that alkoxysilane is pre-hydrolyzed and then condensed to obtain colloidal silica with a dense structure. However, in this method, inorganic acid or organic acid is used to hydrolyze alkoxysilane, and a large amount of anions are introduced, which need to be removed by ion exchange resin later. However, there are still ppm-level anion residues, and anionic impurities may also cause the problem of reduced yield after chip polishing, so high-purity colloidal silica cannot be obtained. There are also complicated ion exchange steps in the process. The ion exchange resin needs to be regenerated and cleaned after use, which will produce a large amount of process wastewater, all of which increase the difficulty and complexity of the process. Patent CN101641288B discloses that alkoxysilane is pre-hydrolyzed and then condensed to obtain dense structure silicon dioxide. Considering the problem of contamination by anionic impurities, pure water is preferentially used to hydrolyze alkoxysilane to obtain hydrolyzate. However, the stability of the hydrolyzate is extremely poor. Generally, it will deteriorate after being left for more than one hour, affecting the use effect. It needs to be prepared and used immediately or stored at low temperature, which consumes a lot of energy and is not conducive to industrial-scale production. Summary of the invention
[0007] The present invention intends to neither use inorganic acid or organic acid to hydrolyze alkoxysilane nor use the process of hydrolyzing alkoxysilane with pure water alone. Using inorganic acid or organic acid to hydrolyze alkoxysilane not only causes the problem of impurity anion contamination, but also involves subsequent complicated anion removal operation steps. When the process of hydrolyzing alkoxysilane with pure water alone is used, the stability of the hydrolyzate is extremely poor and is not suitable for industrial-scale production.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing colloidal silicon dioxide, comprising the following steps:
[0009] 1) adding an organic base solution to ultrapure water, then adding an appropriate amount of alkoxysilane, stirring to obtain a clear and transparent solution, and then adding a stabilizer solution to obtain a hydrolyzate;
[0010] 2) adding an organic base solution to a certain amount of hydrolyzate to obtain a mother solution;
[0011] 3) raising the temperature of the mother liquid to 90-100° C. and keeping the temperature for at least 10 minutes to obtain silicon dioxide crystal nuclei;
[0012] 4) heating the crystal nuclei to boiling, and adding the hydrolyzate dropwise at a pH value of 9.0-10.5 to obtain a dilute silica solution;
[0013] 5) Remove excess water from the dilute silica solution under boiling conditions to obtain colloidal silica.
[0014] As a preferred embodiment of the above technical solution, the organic base is one or more selected from triethanolamine, triisopropanolamine, tetramethylammonium hydroxide, and hydroxyethylethylenediamine.
[0015] As a preferred embodiment of the above technical solution, the concentration of the organic alkali solution is 2.5-4.5%.
[0016] As a preferred embodiment of the above technical solution, the alkoxysilane is electronic grade or methyl orthosilicate or ethyl orthosilicate purified by distillation.
[0017] As a preferred embodiment of the above technical solution, the stabilizer is one or more selected from polyvinyl alcohol, α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin.
[0018] As a preferred embodiment of the above technical solution, the concentration of the stabilizer solution is 0.1-0.5%.
[0019] As a preferred embodiment of the above technical solution, the pH of the hydrolyzate is 8.0-8.5, and the silicon dioxide content in the hydrolyzate is 2.0-4.5%.
[0020] As a preferred embodiment of the above technical solution, the pH value of the mother liquor is 9.5-10.5.
[0021] As a preferred embodiment of the above technical solution, when the hydrolyzate is added dropwise in 4), the dropping speed is 10-25 ml / min.
[0022] The beneficial effects of the present invention are as follows: (1) The preparation method of the present application is simple and convenient, and the process is stable. A high boiling point is used in the preparation process of the mother liquor and the silica nanoparticles. At the same time, the organic base catalyst is not easy to degrade and volatilize at the reaction temperature. The organic base does not contain metal impurities and anionic impurities, and will not cause ionic impurity pollution problems. The organic base is stable at high temperatures and will not cause the situation where the cost needs to be increased due to the loss of the base catalyst. The organic base catalyst is used to hydrolyze alkoxysilane, and a stabilizer solution is added. The obtained hydrolyzate has good stability and remains unchanged for one day at room temperature. Anionic impurities are not introduced, and the cumbersome subsequent impurity removal process is avoided. The present invention can be used to hydrolyze alkoxysilane and stabilize the hydrolyzate by selecting suitable organic bases and stabilizers. At the same time, the organic base is used as a catalyst in the subsequent silica nanoparticle preparation process, which greatly simplifies the process steps and is very suitable for industrial large-scale production.
[0023] (2) The colloidal silica nanoparticles obtained in the present application have high purity, a total metal impurity content of <0.4ppm, good alkali resistance, a pH value of 9.0-10.5, a particle size of 20-80nm, and a solid content of 20-40%, and are very suitable for use in integrated circuit polishing processes. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] 1) Weigh 3500g of ultrapure water in a 5L beaker, add 100g of 2.5wt% triethanolamine solution, stir evenly, add 475g of methyl orthosilicate, continue stirring, the solution changes from oily to clear and transparent, then add 40g of 0.1wt% polyvinyl alcohol solution to obtain a hydrolyzate, the pH value of the hydrolyzate is 8.01, and the silicon dioxide content in the hydrolyzate is 4.52%.
[0027] 2) Add 1500g of the above hydrolyzate to a 5L four-necked flask equipped with a thermometer, a stirring paddle and a condenser, and add 300g of a 2.5wt% triethanolamine solution under stirring to prepare a mother liquor, the pH of which is 9.50. Heat the mother liquor to 90°C and keep it warm for 10 minutes, continue to heat it to boiling, then drip the hydrolyzate through a peristaltic pump, the dripping speed is 25mL / min, the amount of the hydrolyzate added is 7000g, after the hydrolyzate in step 1) is used up, continue to prepare the hydrolyzate according to the method in step 1) for use. During the process of dripping the hydrolyzate, a small amount of 2.5wt% triethanolamine solution can be added to make the pH value of the system between 9.0-10.5. After the hydrolyzate is dripped, remove the excess water in the system under boiling state to obtain concentrated colloidal silica nanoparticles.
[0028] The average particle size of the particles measured by a laser particle size analyzer (dynamic light scattering method) is 20.5 nm, the pH value is 9.03, and the solid content is 20.25%. The total metal content (Al, Ca, Na, K, Fe, Mg, Zn, Ag, Ni, Co, Ti, Cr, Mn, Cu, Pb) measured by inductively coupled plasma mass spectrometry (ICP-MS) is less than 0.4 ppm.
[0029] Example 2
[0030] 1) Weigh 3500g of ultrapure water in a 5L beaker, add 85g of 3.0wt% triisopropanolamine solution, stir evenly, add 355g of ethyl orthosilicate, continue stirring, the solution changes from oily to clear and transparent, then add 10g of 0.2wt% β-cyclodextrin solution to obtain a hydrolyzate, the pH value of the hydrolyzate is 8.12, and the silicon dioxide content in the hydrolyzate is 2.51%.
[0031] 2) 1000g of the above-mentioned hydrolyzate was added to a 5L four-necked flask equipped with a thermometer, a stirring paddle and a condenser tube, and 200g of 3.0wt% triisopropanolamine solution was added under stirring to make a mother liquor, the pH of which was 9.80. The mother liquor was heated to 95°C and kept warm for 10 minutes, and then heated to boiling, and then the hydrolyzate was dripped by a peristaltic pump, and the dripping rate was 20mL / min, and the hydrolyzate dripping amount was 37000g. After the hydrolyzate in step 1) was used completely, the hydrolyzate was prepared by the method in step 1) for standby use. In the process of dripping the hydrolyzate, a small amount of 3.0wt% triisopropanolamine solution can be added to make the system pH value between 9.0-10.5. After the hydrolyzate was dripped, the excess water in the system was removed under boiling state to obtain the colloidal silica nanoparticles after concentration.
[0032] The average particle size of the particles measured by a laser particle size analyzer (dynamic light scattering method) is 45.2 nm, the pH value is 9.75, and the solid content is 25.55%. The total metal content (Al, Ca, Na, K, Fe, Mg, Zn, Ag, Ni, Co, Ti, Cr, Mn, Cu, Pb) measured by inductively coupled plasma mass spectrometry (ICP-MS) is less than 0.4 ppm.
[0033] Example 3
[0034] 1) Weigh 3500 g of ultrapure water in a 5 L beaker, add 105 g of 3.5 wt% tetramethylammonium hydroxide solution, stir evenly, add 360 g of methyl orthosilicate, continue stirring, the solution changes from oily to clear, then add 5 g of 0.35 wt% α-cyclodextrin solution to obtain a hydrolyzate, the pH value of the hydrolyzate is 8.31, and the silicon dioxide content in the hydrolyzate is 3.54%.
[0035] 2) Add 600g of the above hydrolyzate to a 5L four-necked flask equipped with a thermometer, a stirring paddle and a condenser tube, and add 180g of a 3.5wt% tetramethylammonium hydroxide solution under stirring to prepare a mother liquor, the pH of which is 10.00. Heat the mother liquor to 98°C and keep it warm for 10 minutes, continue to heat it to boiling, then drip the hydrolyzate through a peristaltic pump, the dripping speed is 15mL / min, the amount of hydrolyzate added is 45000g, after the hydrolyzate in step 1) is used up, continue to prepare the hydrolyzate according to the method in step 1) for standby use. During the process of dripping the hydrolyzate, a small amount of 3.5wt% tetramethylammonium hydroxide solution can be added to make the pH value of the system between 9.0-10.5. After the hydrolyzate is dripped, remove the excess water in the system under boiling state to obtain concentrated colloidal silica nanoparticles.
[0036] The average particle size of the particles measured by a laser particle size analyzer (dynamic light scattering method) is 60.8 nm, the pH value is 10.25, and the solid content is 35.62%. The total metal content (Al, Ca, Na, K, Fe, Mg, Zn, Ag, Ni, Co, Ti, Cr, Mn, Cu, Pb) measured by inductively coupled plasma mass spectrometry (ICP-MS) is less than 0.4 ppm.
[0037] Example 4
[0038] 1) Weigh 3500 g of ultrapure water in a 5 L beaker, add 85 g of 4.5 wt% hydroxyethylethylenediamine solution, stir evenly, add 300 g of methyl orthosilicate, continue stirring, the solution changes from oily to clear, then add 3 g of 0.5 wt% γ-cyclodextrin solution to obtain a hydrolyzate, the pH value of the hydrolyzate is 8.50, and the silicon dioxide content in the hydrolyzate is 3.00%.
[0039] 2) Add 500g of the above hydrolyzate into a 5L four-necked flask equipped with a thermometer, a stirring paddle and a condenser tube, add 155g of a 4.5wt% hydroxyethylethylenediamine solution under stirring to prepare a mother liquor, the pH of which is 10.50. Heat the mother liquor to 100°C and keep it warm for 10 minutes, continue heating, then drip the hydrolyzate through a peristaltic pump, the dripping speed is 10mL / min, the amount of the hydrolyzate added is 65000g, after the hydrolyzate in step 1) is used up, continue to prepare the hydrolyzate according to the method in step 1) for standby use. In the process of dripping the hydrolyzate, a small amount of 4.5wt% hydroxyethylethylenediamine solution can be added to make the pH value of the system between 9.0-10.5. After the hydrolyzate is dripped, remove the excess water in the system under boiling state to obtain concentrated colloidal silica nanoparticles.
[0040] The average particle size of the particles measured by a laser particle size analyzer (dynamic light scattering method) is 80.2 nm, the pH value is 10.50, and the solid content is 40.21%. The total metal content (Al, Ca, Na, K, Fe, Mg, Zn, Ag, Ni, Co, Ti, Cr, Mn, Cu, Pb) measured by inductively coupled plasma mass spectrometry (ICP-MS) is less than 0.4 ppm.
[0041] It is worth mentioning that the technical features such as the peristaltic pump involved in the patent application of this invention should be regarded as the prior art. The specific structure, working principle and possible control method and spatial layout method of these technical features can be selected by conventional methods in the field and should not be regarded as the inventive point of this patent. This patent will not be further elaborated.
[0042] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the existing technology should be within the scope of protection determined by the claims.
Claims
1. A method for preparing colloidal silicon dioxide, characterized in that: The steps include: 1) adding a certain amount of organic base solution to ultrapure water, then adding an appropriate amount of alkoxysilane, stirring to obtain a clear and transparent solution, and then adding a stabilizer solution to obtain a hydrolyzate; 2) taking another certain amount of organic alkali solution and adding it to a certain amount of hydrolyzate to obtain a mother solution; 3) raising the temperature of the mother liquid to 90-100° C. and keeping the temperature for at least 10 minutes to obtain silicon dioxide crystal nuclei; 4) heating the crystal nuclei to boiling, and adding a certain amount of hydrolyzate to obtain a dilute silica solution at a system pH of 9.0-10.5; 5) Remove excess water from the dilute silica solution under boiling conditions to obtain colloidal silica.
2. The method for preparing colloidal silicon dioxide according to claim 1, characterized in that: The organic base is one or more selected from triethanolamine, triisopropanolamine, tetramethylammonium hydroxide, and hydroxyethylethylenediamine.
3. The method for preparing colloidal silicon dioxide according to claim 2, characterized in that: The concentration of the organic alkali solution is 2.5-4.5%.
4. The method for preparing colloidal silicon dioxide according to claim 1, characterized in that: The alkoxysilane is electronic grade or methyl orthosilicate or ethyl orthosilicate purified by distillation.
5. The method for preparing colloidal silicon dioxide according to claim 1, characterized in that: The stabilizer is one or more selected from polyvinyl alcohol, α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin.
6. The method for preparing colloidal silicon dioxide according to claim 5, characterized in that: The concentration of the stabilizer solution is 0.1-0.5%.
7. The method for preparing colloidal silicon dioxide according to claim 1, characterized in that: The pH value of the hydrolyzate is 8.0-8.5, and the silicon dioxide content in the hydrolyzate is 2.0-4.5%.
8. The method for preparing colloidal silicon dioxide according to claim 1, characterized in that: The mother liquor pH value is 9.5-10.
5.
9. The method for preparing colloidal silicon dioxide according to claim 1, characterized in that: When the hydrolyzate is added dropwise in the step 4), the dropping speed is 10-25 ml / min.
Citation Information
Patent Citations
Method of preparing alkali resistance ultra-pure silicasol
CN101012060A
Colloidal silica, and method for production thereof
CN101641288B
Cited By
Preparation method of SiO2 abrasive with cookie-like special morphology
CN120423563A